Prevalence, Characterization, and Proteomic Relatedness Among β-Lactam-Resistant Bacteria Throughout the Poultry Production Chain in Greece - Anestis Tsitsos; Alexandros Damianos; Konstantinos Kiskinis; Vasilios Tsiouris; Ilias Tirodimos; Nikolaos Soultos; Anna Papa; Vangelis Economou (Foods)
Extended-spectrum-β-lactamase (ESBL) and carbapenemase-producing Escherichia coli, Klebsiella pneumoniae and Acinetobacter spp. are associated with hospital-acquired infections and are commonly isolated across the poultry food production chain. Comprehensive data regarding the prevalence, spatiotemporal variations, and characterization of β-lactam-resistant bacteria in poultry farms and slaughterhouses is scarce. This study examines the prevalence and characteristics of β-lactam-resistant E. coli, K. pneumoniae, and Acinetobacter spp. isolated from poultry farms, slaughterhouses, and associated personnel in Greece. Strains were selectively isolated and identified via MALDI-TOF MS, which was also employed to identify possible relatedness. E. coli isolates were further classified into phylogenetic groups. The prevalence of β-lactam-resistant strains in farm and slaughterhouse environments was 15.0% (n = 15 strains)/57.3% (n = 71 strains) for E. coli, 11.0% (n = 11 strains)/1.6% (n = 2 strains) for K. pneumoniae, and 1.0% (n = 1 strain)/25.8% (n = 38 strains) for Acinetobacter spp., respectively. The prevalence of Acinetobacter spp. and E. coli on farmers’ skin was 16.7% (n = 2 strains) and 8.3% (n = 1 strain), correspondingly. Significantly higher E. coli isolation rates were observed in warmer seasons. All strains were multidrug-resistant and most carried ESBL/AmpC genes. Most E. coli isolates belonged to phylogroups A (41.4%, n = 36) and B1 (24.1%, n = 21). Proteomic analysis indicated relatedness among strains from different regions and seasons. Thus, poultry farms and slaughterhouses may serve as significant reservoirs of β-lactam-resistant strains of E. coli, K. pneumoniae, and Acinetobacter spp.